Oscillation control over light duty cars using magnetic semi-active shock absorbers - Zador, István; Török, Ádám; Vajda, István; Palkovics, László (Transport, 2011)
The present vehicles on the road are equipped with an extended range of actuators, sensors and software controlling dynamics. It is still a difficult problem to solve for a suspension system simultaneously holding the body of the car in comfort and executing requirements imposed for other safety systems like ABS, ESP, steer-by-wire etc. Passive suspension systems are unlikely to provide a solution, and therefore the introduction of semi-active suspensions in practical use is necessary. A possible solution could be a permanent magnetic (PM) synchronous tube generator that can operate as a controllable shock absorber parallel with energy recuperative operation. Design software is realized to calculate geometrical and electrical parameters for arbitrary vehicle suspension systems.First Published Online: 05 Oct 2011